Hubungan Kepuasan Kerja dengan Perilaku Citizenship Organisasional - Rita Rita (Binus Business Review, 2012)
Job satisfaction is a major concern for the organization to achieve effective performance. Each member/employee has citizenship behavior on activities that do and job satisfaction is believed to be related to the behavior of employees. The purpose of this study was to analyze the effect job satisfaction on Organizational Citizenship Behavior (OCB).This study by taking a sample of Non Governmental Organizations (NGO) in Java, which is an organization that is engaged in social and institutional performance is determined by the workers who work to serve the community. Interesting to observe when the OCB research concerning the role of employees in a social institution. So the application of this research carried out by the context in social institutions, especially NGO.The results of multiple regression analysis showed that the positive effect of pay satisfaction on OCB, but the benefits did not significantly affect satisfaction positively on OCB and antecedent factors (pay satisfaction and benefits satisfaction) together - at no significant effect on OCB.